A cruising voyage round the world : first to the South-Seas, thence to the East-Indies and homewards by the Cape of Good Hope ; begun in 1708 and finish'd in 1711. Containing a journal of all the remarkable transactions ..., an account of Alexander Selkirk's living alone four years and four months in an island; and a brief description of several countries in our course noted for trade - Rogers, Woodes (Adam Matthew Digital, 1712)
Includes accounts of many towns and peoples in Central and South America in the early 18th century